An investigation of the antimalarial activity of Artemisia vulgaris leaf extract in a rodent malaria model - Kodippili, Kasun; Daya Ratnasooriya, Wanigasekera; Premakumara, Sirimal; Udagama, Preethi V. (International Journal of Green Pharmacy, 2011)
Antimalarial activity of an organic extract of Artemisia vulgaris was evaluated in this study in terms of both antiparasitic and antidisease activities. Antiparasitic activity of the extract at three doses (250, 500, 1000 mg/kg) was assessed in vivo using the Plasmodium yoelii rodent malaria model, using distilled water as the negative control and Coartem as the positive control. Oral administration of the extract in the 4-day suppressive assay at 500 mg/kg and 1000 mg/kg significantly (P<0.01) inhibited parasitaemia by 65.16% and 51.46%, respectively. Significant (P<0.05) antinociceptive activity was observed for the extract in the hot plate test, indicating a central, supra-spinally mediated response in relieving pain. Anti-disease activity was further corroborated by increased survival of infected mice treated with the 500 mg/kg dose. The A. vulgaris extract was tolerated well by mice over a period of 14 days (assay of sub-chronic toxicity), showing no overt signs of toxicity or stress. Hepatotoxicity (evaluated in terms of serum glutamic-oxaloacetic transaminase (SGOT) and serum glutamic-pyruvic transaminase (SGPT) levels), renotoxicity (in terms of serum urea and creatinine) and haematotoxicity (in terms of total RBC, WBC and differential leukocyte counts) were also ruled out. In conclusion, A. vulgaris leaf extract is orally active, non-toxic and as a weed it has the potential to be a cheap source of plant-based antimalarial in the future.
Keywords: Antimalarial activity; Plasmodium yoelii; Artemisia vulgaris; Sri Lanka; toxicity